2018
DOI: 10.1111/jpm.12502
|View full text |Cite
|
Sign up to set email alerts
|

Implementing recovery‐oriented interventions with staff in a psychiatric hospital: A mixed‐methods study

Abstract: Accessible Summary What is known on the subject? Recovery‐oriented care is a means of providing mental health treatment, focused on the patient's individual needs and active involvement in one's own care. However, this approach presents with challenges, particularly in psychiatric hospitals, which tend to be focused on symptom reduction. What does the paper adds to existing knowledge? This study examines the influence of three different recovery‐oriented training programmes/interventions (namely, illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 49 publications
3
66
0
Order By: Relevance
“…Their positive attitudes to recovery improved (P < 0.01) on exit from placement, with consistent understandings of personal recovery also reported in the qualitative data. While there are no prior reports on recovery attitudes of undergraduate nursing students, these findings are generally consistent with the wider literature in mental health, where clinicians' recovery attitudes have been positive prior to recovery education intervention in health services (total score mean = 3.8 to 4.2), and improved further following education (mean = 4.3-4.4) (Chiba et al 2016;Deane et al 2018;Hornik-Lurie et al 2018). There are no prior studies to compare students' written understandings of personal recovery with; however, our qualitative findings indicated that on placement exit, students developed mental health literacy in terms of using more appropriate language to describe personal recovery.…”
Section: Discussionsupporting
confidence: 82%
“…Their positive attitudes to recovery improved (P < 0.01) on exit from placement, with consistent understandings of personal recovery also reported in the qualitative data. While there are no prior reports on recovery attitudes of undergraduate nursing students, these findings are generally consistent with the wider literature in mental health, where clinicians' recovery attitudes have been positive prior to recovery education intervention in health services (total score mean = 3.8 to 4.2), and improved further following education (mean = 4.3-4.4) (Chiba et al 2016;Deane et al 2018;Hornik-Lurie et al 2018). There are no prior studies to compare students' written understandings of personal recovery with; however, our qualitative findings indicated that on placement exit, students developed mental health literacy in terms of using more appropriate language to describe personal recovery.…”
Section: Discussionsupporting
confidence: 82%
“…However, there is still a lack of implementation of evidence-based treatments in clin- The strengths-based approach included in the definition of the most common class, Coping Assistance, brings us close to the recovery orientation. Recovery orientation has become more central in mental health care during the past 20 years (Hornik-Lurie et al, 2018). Instead of symptom reduction, the emphasis in recovery orientation is on an individual's strengths and in achieving a satisfying life and coping with symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that mental health nurses, despite acknowledging that mental distress is influenced by social/psychodynamic factors, are often constrained by the dominance of the medical model (Carlyle et al ). Hornik‐Lurie et al () reported that mental health nurses only interact with clients for brief periods, often occurs during medication rounds, while other care professionals – such as social workers – spend more time with service users. Hornik‐Lurie et al () also found that medication was perceived as central to the role of the nurse and that other models of care were regarded as ‘fluffy’.…”
Section: Discussionmentioning
confidence: 99%
“…Hornik‐Lurie et al () reported that mental health nurses only interact with clients for brief periods, often occurs during medication rounds, while other care professionals – such as social workers – spend more time with service users. Hornik‐Lurie et al () also found that medication was perceived as central to the role of the nurse and that other models of care were regarded as ‘fluffy’. Other studies have found that mental health nurses want to enhance their knowledge around physical health care (Bolton et al ), indicating that there may be a preference for a return to a more medical approach to care, but also that there are perceived deficits in this area.…”
Section: Discussionmentioning
confidence: 99%